Review on MXenes-Based Electrocatalysts for High-Energy-Density Lithium–Sulfur Batteries - Xintao Zuo; Yanhui Qiu; Mengmeng Zhen; Dapeng Liu; Yu Zhang (Nano-Micro Letters)
Highlights The significance and challenges associated with high-sulfur loading and lean electrolytes in lithium–sulfur batteries are comprehensively reviewed. Catalytic properties of MXenes-based electrocatalysts are optimized via d-band center tuning, internal electric field constructing, single-atom seeding, and cocktail effects introducing. The structure–activity relationships between MXenes-based electrocatalysts and lithium–sulfur battery performances are comprehensively summarized.